Integration of Alternative Polymer Based Materials into Clutch Disc Stopper (Aintelia Science Notes, 2022)
Dry friction clutches continue to be actively used especially in heavy commercial vehicles today. With the increase in electrification processes of vehicle power groups, the transition of dry friction clutches, which have decreased in passenger vehicles, to commercial vehicles does not seem possible with today's technology. In order to prevent emission values ​​that are tried to be minimized in today's world, integrating innovative materials into conventional systems as well as different power generation methods developed, also emerges as a suitable solution for the near future. In our study, it was aimed to derive new alternatives for the stopper part, which is one of the dry friction clutch parts that continues to be produced and used with conventional metal products. In this context, alternative product design, testing and validation were carried out using innovative production techniques and polymer composite materials. The main goal of this study was to show that in addition to radical changes that take many years in existing systems, weight reductions and related harmful effects can be achieved in a short time with the use of new materials. Within the scope of the study, structural analyses of the stopper element were performed with the ANSYS Workbench program. The tests performed for the designed alternative product confirm the structural analysis results. The analysis and test results show that the alternatively designed stopper is resistant to working conditions and the innovative work performed allowed a 14% reduction in the stopper weight.